A Knowledge-Based Performance Management System Framework: Case Study in The Medical Device Manufacturing Sector - A. Rizky Aulia Utami; Dermawan Wibisono (Green Publisher Indonesia, 2026)
The company operated in a highly regulated medical device environment where quality consistency, documentation accuracy, and supply reliability were essential to meeting ISO 13485 and MDR requirements. As annual purchasing volumes increased, the organization became heavily dependent on international suppliers, with more than 95% of raw materials sourced overseas. The main operational issue examined in this study was the high rate of late supplier deliveries: 53.83% arrived after the agreed schedule between 2020 and 2024, representing USD 2,003,408.53 in purchase value, while only 45.76% were on time and 0.40% arrived early. These delays disrupted production scheduling, weakened the company’s ability to meet customer orders, and undermined operational credibility, particularly within the procurement function. This research aimed to address two key problems: identifying the underlying causes of procurement inefficiencies and designing a Knowledge-Based Performance Management System (KBPMS) tailored to the company’s operational context. A qualitative-dominant mixed-method approach was adopted. Primary data were collected through semi-structured interviews and questionnaire surveys. Secondary data were sourced from historical purchasing records, supplier delivery reports, internal SOPs, and departmental objectives to support a comprehensive understanding of procurement challenges. The analysis process consisted of three stages. First, root cause analysis was conducted using the Ishikawa diagram. Second, the KBPMS framework was developed to define the criteria.